Interações discursivas em aulas de química : relações com o engajamento dos alunos - Silva, Cátia Pereira da (2015)
This research had as main objective analyze the enunciative strategies articulated by a teacher in a chemistry classroom, identifying their contributions to students‟ engagement along the thematic sequence polymers . The research consists in a case study, concerning the analysis to the performance of the 3º year of the secondary education, in a private school located in Aracaju Sergipe. We used as data collection methods: Recording the lessons in the class on video, interviews and field notes. We consider that the recordings have had quite an importance in this work, since from them we transcripts of speeches and selected the desired categories, getting the time concerning the use of each of them in analysis of lessons, using a video player called Windows Media Player. We calculate the estimated time of each category and obtained the quantitative dimension of research. The qualitative dimension occurred through analysis of episode maps, discursive sequences and transcriptions of representative episodes of the speeches from teachers and students. The data analysis was done by analytical tool proposed by Mortimer and Scott (2002) and amplified by Mortimer et al (2007). This allowed us to reveal the interactive dynamics and speech flows that characterized the classroom. The analysis was based on the theories of Vygotsky and Bakhtin, as these thinkers, guide us in order to understand the value of the environment and interactions between individuals dialogical. The intentions of the teacher varies with the passing of time, combined to the kinds of communicative approach used. We observed that although the teacher encourage interaction in the classroom with several examples of daily life, the dialogical interactions were reduced when compared to the authority, What did not interfere with the quality of the scientific content and approach or the level of satisfaction in the students. We consider that this work contributes to increased knowledge about discursive dynamics in chemistry classes.